Therapeutic reduction of lysophospholipids in the digestive tract recapitulates the metabolic benefits of bariatric surgery and promotes diabetes remission - James G. Cash; Eddy Konaniah; Narasimha Hegde; David G. Kuhel; Miki Watanabe; Lindsey Romick-Rosendale; David Y. Hui (Elsevier, 2018)
Objective: Obesity and obesity-related metabolic disorders are major health problems worldwide. The most effective obesity intervention is bariatric surgery. This study tested the hypothesis that bariatric surgery alters phospholipid metabolism in the gastrointestinal tract to favor a metabolically healthy gut microbiota profile and therapeutic intervention of phospholipid metabolism in the gastrointestinal may have similar metabolic benefits. Methods: The first study compared plasma levels of the bioactive lipid metabolites lysophospholipid and trimethylamine N-oxide (TMAO) as well as gut microbiota profile in high fat/carbohydrate (HFHC) diet-fed C57BL/6 mice with or without vertical sleeve gastrectomy (VSG) and in Pla2g1b−/− mice with group 1B phospholipase A2 gene inactivation. The second study examined the effectiveness of the non-absorbable secretory phospholipase A2 inhibitor methyl indoxam to reverse hyperglycemia and hyperlipidemia in HFHC diet-fed C57BL/6 mice after diabetes onset. Results: Both bariatric surgery and PLA2G1B inactivation were shown to reduce lysophospholipid content in the gastrointestinal tract, resulting in resistance to HFHC diet-induced alterations of the gut microbiota, reduction of the cardiovascular risk factors hyperlipidemia and TMAO, decreased adiposity, and prevention of HFHC diet-induced diabetes. Importantly, treatment of wild type mice with methyl indoxam after HFHC diet-induced onset of hyperlipidemia and hyperglycemia effectively restored normal plasma lipid and glucose levels and replicated the metabolic benefits of VSG surgery with diabetes remission and TMAO reduction. Conclusion: These results provided pre-clinical evidence that PLA2G1B inhibition in the digestive tract may be a viable alternative option to bariatric surgery for obesity and obesity-related cardiometabolic disorder intervention. Keywords: Phospholipase A2, Gut microbiota, Cardiometabolic disease, Bariatric surgery, Lysophospholipid